The Canada goose (Branta Canadensis) : an annotated bibliography - Craven, Scott R.; U.S. Fish and Wildlife Service. (Washington, D.C. : U.S. Dept. of the Interior, Fish and Wildlife Service, 1981)
Includes index. Mode of access: Internet.